SOCIO-ECONOMIC DIFFERENTIATION OF MUNICIPAL ENTITIES OF THE IRKUTSK REGION (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
The research shows that there is a tendency towards increasing territorial differentiation at the municipal level of the Irkutsk Region in terms of socio-economic well-being. This can negatively affect the quality of functioning of the regional economy and social security of the population. The article analyzes a number of indicators that determine the level of well-being of territories and affect inter-municipal differentiation.
Keywords: differentiation; municipalities; socio-economic indicators; level of well-being